2020
DOI: 10.1186/s13018-020-01642-5
|View full text |Cite
|
Sign up to set email alerts
|

The outcome for surgical fixation of distal radial fractures in patients with idiopathic Parkinson’s disease: a cohort study

Abstract: Introduction Idiopathic Parkinson’s disease (PD) is a progressive neurologic disorder causing postural instability and unsteady gait. These patients are at increased risk for fractures and have inferior outcomes after treatment. Several studies have evaluated the incidence and outcome of PD patients after hip fractures. However, there are limited studies assessing the outcome of upper extremity fractures in these patients. In this study, we evaluated the outcome of PD patients that received sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 18 publications
1
9
1
Order By: Relevance
“…Primary, DRFs have a very low nonunion or malunion rate (0.2–10%), but this study revealed very high failure rates for PD patients (15.8%) 12 , 18 . In a previous study conducted by our group, the treatment failure rate after DRF in PD can be as high as 39%, with loss of reduction and malunion of fracture being the two most frequent mechanisms 12 . When compared with non-PD patients, k-wires and external fixation appeared to have inferior results for PD, while plating of the radius had similar success rates.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…Primary, DRFs have a very low nonunion or malunion rate (0.2–10%), but this study revealed very high failure rates for PD patients (15.8%) 12 , 18 . In a previous study conducted by our group, the treatment failure rate after DRF in PD can be as high as 39%, with loss of reduction and malunion of fracture being the two most frequent mechanisms 12 . When compared with non-PD patients, k-wires and external fixation appeared to have inferior results for PD, while plating of the radius had similar success rates.…”
Section: Introductionmentioning
confidence: 54%
“…delayed functional recovery, longer hospital stays, and increased revision surgeries) in comparison with non-PD patients after orthopaedic procedures 6 , 7 , 10 , 11 . In current literature, there are very few studies evaluating the outcome for upper extremity fractures (UEF) that occurred in PD 12 15 . Our team recently reported the outcome of distal radial fractures after surgical fixation for PD 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Chou et al [2] evaluated the outcomes after surgery for distal radius fracture in which all underwent open reduction and internal fixation (ORIF). The treatment failure rate was 39.1% (PD) and 4.6% (non-PD).…”
mentioning
confidence: 99%